2010
DOI: 10.1007/s00414-010-0438-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of post-mortem computed tomography in the investigation of intentional neonatal upper airway obstruction: an illustrated case

Abstract: We present a single case report illustrating the diagnostic role of multi-slice computed tomography (MSCT) in the investigation of suspicious child death where mechanical asphyxia is suspected. The case illustrates how radiological findings that may not be observable on conventional plain X-ray were identified by post-mortem MSCT. We illustrate how MSCT can illustrate the position of a foreign body within the upper airway of a neonate without the need for in situ dissection and how the combination of post-mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Authors have reported the use of PMCT for the investigation of foreign bodies in the upper respiratory tract in both adults and neonates. 57,58 Summary The use of PMCT is rapidly expanding within both natural and unnatural death investigation. Although there is a growing literature promoting its use in post-mortem examinations the evidence base as to its final potential role remains deficient to date.…”
Section: Head Injurymentioning
confidence: 99%
“…Authors have reported the use of PMCT for the investigation of foreign bodies in the upper respiratory tract in both adults and neonates. 57,58 Summary The use of PMCT is rapidly expanding within both natural and unnatural death investigation. Although there is a growing literature promoting its use in post-mortem examinations the evidence base as to its final potential role remains deficient to date.…”
Section: Head Injurymentioning
confidence: 99%
“…Although VA using MSCT was able to detect the presence and location of foreign bodies, it fails to identify the type and number of foreign bodies present. 11 This small piece of evidence has great medico-legal significance, which recommends VA to be best used as an adjunct to CA to obtain optimum results in such instances. Furthermore, 39% of false negatives were observed when using PMCT in the investigation of asphyxial deaths proving its limited value in such cases.…”
Section: Discussionmentioning
confidence: 99%